Effect of the manganese-cobalt substitution on the micro-hardness and thermal properties of zinc phosphate glasses. (2022) - Jerroudi, M.; Bih, L.; Ouachouo, L.
Highlights: Elaboration of glasses inside the system ZnO-CoO-MnO2 -P2 O5 . The physical parameters including density, molar volume and ionocovalent crosslink density are determined. Investigation of the thermal parameters using DSC technique. The micro-hardness values are determined for each glass. Abstract: Metaphosphate glasses belonging to the 10ZnO-(40-x)CoO-xMnO2 -50P2 O5 system, with 0 ≤ x ≤ 40 mol%, have been synthesized by the melt-quenching technique. The obtained glasses are colored. Some physical parameters such as density, molar volume, and packing oxygen density are determined. It is observed that all these parameters are composition-dependent. The density and molar volume decrease and increase as MnO2 content increases, respectively. Thermal properties were studied with a differential thermal analysis. The glass transition temperature (Tg ), crystallization temperature (Tc ), and the thermal stability (ΔT) of each glass are evaluated. It is found that glass transition temperature (Tg ) and the ionocovalent crosslink density (ICd ) decrease with increasing the Mn/Co ratio. It is worth noting that the highest value the thermal stability (ΔT = 192 °C) is obtained for the glass containing high-MnO2 content (x = 30 mol %). The effect of MnO2 on the rigidity of the glasses is also studied by the determination of the micro-hardness (Hv ) values. It is observed that this parameter increases with increasing of MnO2 content. This trend is explained according to the bond strength.